Frequency and Characteristics of Medical Complications in Rehabilitation Settings: A Scoping Review - Elyse Ladbrook; Stephane Bouchoucha; Ana Hutchinson (Medical Journals Sweden, 2022)
Objective: To synthesize the available evidence on medical complications occurring in adult patients in subacute inpatient rehabilitation, and to describe the impact on subacute length of stay and readmission to acute care. Design: Scoping review. Subjects: Adult patients, within the inpatient rehabilitation environment, who experienced medical complications, clinical deterioration and/or the requirement of transfer to acute care. Methods: A systematic search of MEDLINE and CINAHL electronic databases was undertaken to identify primary research studies published in English and French during the period 2000-2021. Study reporting followed the standards indicated by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews checklist (PRISMA-ScR). Results: A total of 47 studies were identified for inclusion. Key results included differences in the type and frequency of complications according to admission type, the proportion of patients experiencing at least 1 complication, and complications associated with transfer to acute care. Conclusion: Patients admitted for inpatient rehabilitation are at high risk of medical complications and may not be medically stable during their admission, requiring care by clinicians with expertise in functional rehabilitation, and ongoing management by members of the multidisciplinary team with expertise in acute general medicine, infectious diseases and recognition and response to clinical deterioration. LAY ABSTRACT Medical complications are associated with negative patient health outcomes and significant impact on healthcare utilization and delivery. A review was undertaken to scope available literature and explore medical complications as an important concept in relation to healthcare delivery and utilization for patients admitted to subacute care for inpatient rehabilitation. The results of the review highlighted that patients admitted for inpatient rehabilitation are at high risk of medical complications, with infections, neurological and cardiorespiratory complications being prominent. Patients admitted following stroke, traumatic brain injury/trauma or cancer are particularly vulnerable. The findings of this review emphasize the importance of including clinicians within the multidisciplinary rehabilitation team who have expertise in acute medicine and nursing, infection prevention and control, and recognition and response to clinical deterioration, to support the delivery of high-quality and safe care within inpatient subacute settings.